Characteristics, functions, and applications of metallothionein in aquatic vertebrates - Wang, Wei-Chao; Mao, Huan; Ma, Dan-Dan; Yang, Wan-Xi (Frontiers in Marine Science, 2014)
The documents on Metallothioneins (MTs) in aquatic creatures, especially focusing on their function as biomarkers in environmental monitoring programmes, are vast and increasing. There are, however, few papers to summary the physiological role of MTs in aquatic organisms especially on development. The multifaceted roles of MTs include involvement in homeostasis, protection against heavy metals and oxidant damages, and metabolic regulation, sequestration and/or redox control. In this paper, we have collected published information on MTs in aquatic organisms—pisces, amphibians, mammals etc, and analyzed their function in these aquatic animals. MTs have four main functions in aquatic vertebrate. They are respectively bioaccumulation of toxic metals and detoxiﬁcation, homeostatic regulation of metals, protection against oxidative stress and neuroprotective mechanism. MTs separate in different tissues and they have various distributions in different tissues of aquatic vertebrate, including liver, gills, kidney, testes and brain. MTs can be induced by a variety of environmental and physiological factors, among which, heavy metals are the main kind of MTs inducers in aquatic vertebrate. Here we pay more attention on the essential metals copper (Cu) and zinc (Zn) and the non-essential metals cadmium (Cd), silver (Ag), lead (Pb) and mercury (Hg).